The generation game: Governing through bio-politics. Issue 1 (February 2021) - Reed, Cara; Thomas, Robyn
An increasingly popular management tool is to stratify a workforce along generational lines, to distinguish its qualities and differentiate orientations to work. From this, a range of organisational practices, ranging from leadership styles to reward systems are tailored to fit specific generational characteristics. We term this practice 'management-by-generation' and examine how it has the potential to govern as a bio-political technology. The article develops nascent work within organisation studies on governmentality and bio-politics to demonstrate the powerful potential of management-by-generation to govern in contemporary organisations. In line with other Foucauldian studies on ageing, it also contributes to the research on generations in demonstrating how a bio-political construction of generation allows management-by-generation to govern effectively, while more sociologically informed conceptualisations of generation could be a source of contestation to this emerging technology.